Appropriate targeting of artemisinin‐based combination therapy by community health workers using malaria rapid diagnostic tests: findings from randomized trials in two contrasting areas of high and low malaria transmission in south‐western Uganda. Issue 9 (9th August 2016) - Ndyomugyenyi, Richard; Magnussen, Pascal; Lal, Sham; Hansen, Kristian; Clarke, Siân E.
Abstract: Objective: To compare the impact of malaria rapid diagnostic tests (mRDTs), used by community health workers (CHWs), on the proportion of children <5 years of age receiving appropriately targeted treatment with artemisinin‐based combination therapy (ACT), vs. presumptive treatment. Methods: Cluster‐randomized trials were conducted in two contrasting areas of moderate‐to‐high and low malaria transmission in rural Uganda. Each trial examined the effectiveness of mRDTs in the management of malaria and targeting of ACTs by CHWs comparing two diagnostic approaches: (i) presumptive clinical diagnosis of malaria [control arm] and (ii) confirmatory diagnosis with mRDTs followed by ACT treatment for positive patients [intervention arm], with village as the unit of randomisation. Treatment decisions by CHWs were validated by microscopy on a reference blood slide collected at the time of consultation, to compare the proportion of children <5 years receiving appropriately targeted ACT treatment, defined as patients with microscopically‐confirmed presence of parasites in a peripheral blood smear receiving artemether‐lumefantrine or rectal artesunate, and patients with no malaria parasites not given ACT. Results: In the moderate‐to‐high transmission area, ACT treatment was appropriately targeted in 79.3% (520/656) of children seen by CHWs using mRDTs to diagnose malaria, vs . 30.8% (215/699) of children seen by CHWs using presumptive diagnosis ( P < 0.001). In the low transmission area, 90.1% (363/403) children seen by CHWs using mRDTs received appropriately targeted ACT treatment vs . 7.8% (64/817) seen by CHWs using presumptive diagnosis ( P < 0.001). Low mRDT sensitivity in children with low‐density parasitaemia (<200 parasites/ μ l) was identified as a potential concern. Conclusion: When equipped with mRDTs, ACT treatments delivered by CHWs are more accurately targeted to children with malaria parasites. mRDT use could play an important role in reducing overdiagnosis of malaria and improving fever case management within iCCM, in both moderate‐to‐high and low transmission areas. Nonetheless, missed treatments due to the low sensitivity of current mRDTs in patients with low parasite density are a concern. For community‐based treatment in areas of low transmission and/or non‐immune populations, presumptive treatment of all fevers as malaria may be advisable, until more sensitive diagnostic assays, suitable for routine use by CHWs in remote settings, become available.